Edward R. Murrow with, from left to right: Unidentified, Governor Theodore R. McKeldin, and Hammerman (far right). At ceremony where Murrow received his citation for honorary citizen for State of Maryland. (Tufts Archival Research Center, 2005)
8x10. February 2, 1957.